Interface dominated mechanical properties of ultra-fine grained and nanoporous Au at elevated temperatures. (December 2016) - Leitner, A.; Maier-Kiener, V.; Jeong, J.; Abad, M.D.; Hosemann, P.; Oh, S.H.; Kiener, D.
Abstract: Modern design and engineering of highly efficient devices and machines demand innovative materials to satisfy requirements such as high strength at low density. The purpose of this study was to oppose the mechanical properties and deformation behavior of ultra-fine grained Au to those of nanoporous Au, to study the influence of different types of interfaces. Microstructural investigations of the foam surrendered a ligament size of ∼100 nm which themselves consist of 70 nm grains in average, while the ultra-fine grained gold features a mean grain size of 325 nm. Nanoindentation lends itself as a convenient technique to obtain material properties at ambient as well as high temperature conditions. In this work, a substantial indentation test series was performed in order to determine hardness, Young's modulus, strain-rate sensitivity and activation volume at room and elevated temperatures up to 300 °C. On account of the small characteristic dimensions, high hardness values were noted for both materials, which rapidly drop at elevated temperature. Additionally, an enhanced strain-rate sensitivity accompanied by low activation volumes was determined at room temperature, which further increased at elevated temperatures. This behavior is associated with thermally activated interactions between dislocations and interfaces. For nanoporous Au, due to the presence of free surfaces, a considerable increase of hardness was observed upon annealing. This can be attributed to a reduced number of mobile dislocations in the material after annealing, as supported by implemented porosity maps on indent cross-sections, showing distinct differences for tests at varying temperature. Graphical abstract: